Magnetic Nanoparticles and Magnetic Field Exposure Enhances Chondrogenesis of Human Adipose Derived Mesenchymal Stem Cells But Not of Wharton Jelly Mesenchymal Stem Cells - Labusca, Luminita; Herea, Dumitru-Daniel; Emanuela Minuti, Anca; Stavila, Cristina; Danceanu, Camelia; Plamadeala, Petru; Chiriac, Horia; Lupu, Nicoleta (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: Iron oxide based magnetic nanoparticles (MNP) are versatile tools in biology and medicine. Adipose derived mesenchymal stem cells (ADSC) and Wharton Jelly mesenchymal stem cells (WJMSC) are currently tested in different strategies for regenerative regenerative medicine (RM) purposes. Their superiority compared to other mesenchymal stem cell consists in larger availability, and superior proliferative and differentiation potential. Magnetic field (MF) exposure of MNP-loaded ADSC has been proposed as a method to deliver mechanical stimulation for increasing conversion to musculoskeletal lineages. In this study, we investigated comparatively chondrogenic conversion of ADSC-MNP and WJMSC with or without MF exposure in order to identify the most appropriate cell source and differentiation protocol for future cartilage engineering strategies. Methods: Human primary ADSC and WJMSC from various donors were loaded with proprietary uncoated MNP. The in vitro effect on proliferation and cellular senescence (beta galactosidase assay) in long term culture was assessed. In vitro chondrogenic differentiation in pellet culture system, with or without MF exposure, was assessed using pellet histology (Safranin O staining) as well as quantitative evaluation of glycosaminoglycan (GAG) deposition per cell. Results: ADSC-MNP complexes displayed superior proliferative capability and decreased senescence after long term (28 days) culture in vitro compared to non-loaded ADSC and to WJMSC-MNP. Significant increase in chondrogenesis conversion in terms of GAG/cell ratio could be observed in ADSC-MNP. MF exposure increased glycosaminoglycan deposition in MNP-loaded ADSC, but not in WJMSC. Conclusion: ADSC-MNP display decreased cellular senescence and superior chondrogenic capability in vitro compared to non-loaded cells as well as to WJMSC-MNP. MF exposure further increases ADSC-MNP chondrogenesis in ADSC, but not in WJMSC. Loading ADSC with MNP can derive a successful procedure for obtaining improved chondrogenesis in ADSC. Further in vivo studies are needed to confirm the utility of ADSC-MNP complexes for cartilage engineering.